A Profile of New Zealand Crossbred Wool Clip in Both Greasy and Scoured Forms in the 2017-18, 2018-19, and 2019-20 Seasons. Issue 13 (1st December 2022) - Baxter, Peter; Wear, Jeremy
ABSTRACT: New Zealand is the third-largest producer of wool in the world and accounts for approximately 9.3% of world production (approx. 140, 000 tonnes greasy annually). We describe the properties of the New Zealand crossbred wool clip over the 2017–18, 2018–19, and 2019–20 seasons and compare the statistics from the greasy farm lots with data obtained from consignments of scoured wool. Monthly average values of diameter, vegetable matter, and color exhibit seasonality, and despite the fact that approximately 30% of the wool is exported in its greasy state, the remaining 70% scoured onshore still adequately represents the body of the clip, with still some degree of seasonality, but with changes in the distribution of diameters of consignments (but not the overall averages), and improvements in color. Additionally, we demonstrate that despite the replacement of nonylphenolethoxylate (NPEO) by more environmental-friendly detergents, the levels of residual ash and grease in the scoured wool consignments show improvement over those reported in 2003 and 2007.